Social marketing: imperatives for rural entrepreneurship - Liudmyla Tarasovych; Maryna Yaremova; Tetiana Usiuk; Svitlana Lavrynenko; Anna Slobodianyk; George Abuselidze (E3S Web of Conferences, 2023)
The article substantiates the idea that the implementation of the marketing paradigm in the social sphere is taking on increasing importance in order to address the urgent social issues that Ukraine will undoubtedly face in the near future, in addition to its economic and political issues. What is meant here is the concept of social marketing, whose dominant idea is the harmonious integration of three elements: public interests, consumer needs, and the profit of business entities. A new model of entrepreneurship is described from the standpoint of business coherence and solving social challenges. The advantages of using social marketing technologies and the program as a strategic approach to setting up and running businesses in rural areas are substantiated in the context of their implication in the process of addressing social issues and ensuring public welfare. The practical value of the study lies in the scientific substantiation of the need for and benefits of social marketing for rural entrepreneurship due to the possibility of its conceptualization as a function of social management, a special marketing activity of business entities, a planned tool for regulating the market economy, and a social policy tool. Further research is aimed at the development of quantitative and qualitative criteria for evaluating the effect of the implementation of social technologies and programs, with further testing of the obtained results.
Keywords: 330